In silico discovery of a neutral 2π aromatic silicon aluminum compound - Sharma, Himanshu; Vanka, Kumar (Organometallics, 2024)
The recently developed ab initio nanoreactor (AINR) approach to identifying reaction intermediates and pathways without the necessity of experimental input has been employed in the current work to locate new cyclic silicon-based structures that have the potential to display aromaticity. Using this approach, we have identified many cyclic silicon-based molecules that have been experimentally reported over the past three decades. More importantly, the current work showcases an interesting new molecule that has been discovered through this approach: a four-membered cyclic compound of silicon and aluminum that displays significant 2 pi aromaticity and is capable of the activation of important small molecules such as ammonia.